An iterative algorithm for solving split equilibrium problems and split equality variational inclusions for a class of nonexpansive-type maps. (2nd November 2018) - Chidume, C. E.; Romanus, O. M.; Nnyaba, U. V.
ABSTRACT: In this paper, an iterative algorithm that approximates solutions of split equality fixed point problems (SEFPP) for quasi- φ -nonexpansive maps is constructed. Strong convergence of the sequence generated by this algorithm is established in certain real Banach spaces without imposing any compactness-type condition on either the operators or the space considered. We applied our theorem to solve split equality problem, split equality variational inclusion problem and split equality equilibrium problem . Furthermore, some numerical example is given to demonstrate the implementability of our algorithm. Finally, our theorems improve and complement a host of important recent results.